Precision motion and energy exchange control on robot’s leg interaction with soft surface - Wan Mohd Nafis, Wan Lezaini (2019)
Nowadays, various ideas have been presented in developing bio-inspired robot such as legged, flying, swimming and other crawling mechanisms. Generally legged robot development and control covered beyond manipulation issues in which stability of the overall system need to be catered as well. Stable leg manipulation for a legged robot becomes a priority to guarantee the whole system stability. One of the challenges in legged robot manipulation control is to sustain the leg’s joint angular motion precision. As the number of degrees of freedom for a leg is increased, the demand for robust control becomes higher since it requires precise coordination in foot workspace. Besides that, the nonlinearity factor in robot’s leg motion also need to be tackled to ensure the overall stability of a legged robot especially during walking on uneven terrain. Popular method such as impedance control has been extensively used by understanding dynamic interaction between leg tips and the environment. Most of the researched had emphasized on dynamic control that is able to reposition robot’s foot placement during walking on the unstructured terrain with hard surfaces. This method may not be suitable for soft surface that required robot’s leg to withstand the ground medium while pushing its body although repositioning was done. As a result, the overturning may happen to the robot since the robot’s foot will slip due to the low energy to adapt with environment surface stiffness. Here, there are two problem statements which are implication of imprecision of leg joint motion and uncontrollable energy exchange in foot dynamic motion. Therefore, this study has taken initiative to propose two solutions for the aforementioned issues which are hybrid Proportional Integral-Antiwindup-Fuzzy Logic Control-Derivative (PIA-FLC-D) and impedance control respectively. PIA-FLC-D is proposed to overcome leg’s joint precision affected by nonlinear gravitational factor. On the other hand, impedance control is derived to cater the velocity shaping as indirectly controlling the energy exchange of the leg specifically at leg dragging period. A bio-inspired robot named Hexapod-to-Quadruped (Hexaquad) robot is used as the targeted platform for verification and validation. The proposed PIA-FLC-D was verified and the results were compared with the predecessor controllers. The results show that PIA-FLC-D performs fast response with only 0.1s delay compared to its predecessor controller with 0.25s delay during trajectory tracking. For the case of the impedance control, the results show that Hexaquad’s leg velocity increases with the contact force on vertical position in which resulting energy increased on the leg while maintaining the overall leg motion shape. The same Hexaquad’s leg that applied the proposed impedance controller also tested completing the walking motion on the soft surface medium (dry sand) while bearing the robot’s body weight. The results showed that during drag sequence, by using the proposed controller, each joint of Hexaquad’s leg manage to follow the reference motion precisely compared to without using the proposed controller.